PRODUCTION DIVESTMENTS ON FARMS - ESSENCE, SCOPE, CONSEQUENCES - Wojewodzic, Tomasz; Płonka, Aleksandra (Acta Scientiarum Polonorum. Oeconomia, 2015)
The purpose of the paper is to identify changes occurring on farms in relation to the limitation of their production activities. Considerable attention was paid to changes affecting the scale and organization of livestock production in regard of which recessive phenomena have been particularly visible in recent years. Observed at the beginning of the 21st century process of withdrawing Polish farmers from agricultural production should be considered a sign of structural change in agriculture. Farmers' abandonment of livestock production can be both a transitional stage of resigning from agricultural activities (palliative divestments) as well an initial stage for the farm's re-organization (repositioning, reconcentration).